Pelatihan pembuatan sabun cair cuci tangan untuk mencegah penyakit covid-19 dan hepatitis pada sekolah dasar di Kabupaten Parigi Moutong - Mustafa Mustafa; A. Bungawati; Maryam Maryam (Universitas Mataram, 2023)
Community service carried out by providing training in making liquid hand washing soap in elementary schools is the first step that can be taken to prevent Covid-19 and Hepatitis in elementary school children. The community service activities are carried out using various methods, namely by identifying or surveying existing partners, providing counseling and providing the practice of making liquid hand washing soap. The number of participants in community service was 30 participants consisting of students and teachers. The results of the community service activities, the participants welcomed enthusiastically and made an active contribution in participating in the training activities with the hope that the participants could carry out the stages of making liquid hand washing soap independently from the training that had been given.